2014
DOI: 10.1175/wcas-d-12-00062.1
|View full text |Cite
|
Sign up to set email alerts
|

Unrealized Potential: A Review of Perceptions and Use of Weather and Climate Information in Agricultural Decision Making

Abstract: This article reviews research on agricultural decision makers’ use and perceptions of weather and climate information and decision support tools (DSTs) conducted in the United States, Australia, and Canada over the past 30 years. Forty–seven relevant articles, with locations as diverse as Australian rangelands and the southeastern United States, ranging in focus from corn to cattle, were identified. NVivo 9 software was used to code research methods, type of climate information explored, barriers to broader us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 57 publications
5
101
0
1
Order By: Relevance
“…Eisenack et al 2014;Mase and Prokopy 2014;Jones et al 2016). Some limited research has been conducted on the interdependencies between barriers and the dynamic changes that affect them (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eisenack et al 2014;Mase and Prokopy 2014;Jones et al 2016). Some limited research has been conducted on the interdependencies between barriers and the dynamic changes that affect them (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The need to understand and work within stakeholders' existing decision-making processes is well established in the literature (e.g. Mase and Prokopy 2014;Howden and Jacobs 2015). Although the decision-centred framework is increasingly acknowledged as resulting in better decision-making than the climate-centred framework (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…On a related note, there is insufficient research on the role of climate in farmer decision-making in California (Nicholas and Durham 2012;Niles et al 2013) and countrywide (Mase and Prokopy 2014). One California study suggested that farmers were more likely to pursue adaptation actions if they perceived climate change as being a proximate and relevant phenomenon, but many did not .…”
Section: Opportunities For Future Researchmentioning
confidence: 99%
“…Agricultural systems are complex, and producers are generally experienced in integrating many different considerations into a single decision (Mase and Prokopy, 2014). Often, a focus on short-term improvements and regulatory actions can have unintended negative impacts on other parts of the production system or the environment.…”
Section: Priorities For Partnerships and Communication Among Researchmentioning
confidence: 99%